?GENE ACTION FOR SOME QUANTITATIVE CHARACTERS IN UPLAND COTTON (GOSSYPIUM HIRSUTUM L.) - Ahmed, Mushtaque; Kalwar, Muhammad Shaban; Baloch, G M (Biological Sciences - PJSIR, 2003)
The study, includes a six-parent complete diallel cross of varieties/lines viz. CRIS-15, TH-3/83, TH-28/83, CRIS-9, NIAB-78 and Rehmani of Gossypium hirsutum L. It was initiated to determine the genetics of lint weight, seed index, staple length and seed cotton yield per plant. The WrVr graph showed that, lint weight and seed cotton yield were conditioned by over-dominance, while seed index and staple length by partial-dominance type of gene action. CRIS-9 and NIAB-78 x CRIS-9 appeared to be best general and specific combiners, respectively. Hence, they are recommended for future breeding programme.